Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(i) (x + 3) (x + 7)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(4x + 5) (4x + 1)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(4x - 5) (4x - 1)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(4x + 5) (4x - 1)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(2x +5y) (2x + 3y)
(2x +5y) (2x + 3y) = (2x)2 + (5y + 3y)2x + (5y x 3y)
                         = 4x2 + (5 + 3)y x 2x + 15y2
                         = 4x2 + (5 + 3)y x 2x + 15y2  Â
                         = 4x2 + [8y x 2x ]+ 15y2
                         = 4x2 + 16yx + 15y2
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(2a2 + 9) (2a2 + 5)
Use the identity (x + a)(x + b) = x2 + (a + b)x + ab to find the following products.
(xyz - 4) (xyz - 2)